Integrating Animated Videos into Arabic Reading Textbook Development: A Pedagogical Approach - Nadhif Hibatullah; Anisatu Thoyyibah; Muhammad Ainur Roziqi; Shaim Hamissou Malam Mohamed (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2026)
This study aimed to develop an Arabic textbook, namely, Al-Qirā'ah Al-Rasyīdah based on animated video and examine its effectiveness in muṭāla'ah (reading) learning. This research used a Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The sample of this research was class VIII students of MTs Muhammadiyah 2 Al-Munawwaroh Malang. The data collection methods used were interviews, questionnaires and tests. The data analysis technique used was descriptive analysis, paired t-test and effectiveness test using the N-gain. The results of this study were: (1) The development of Arabic reading textbooks through the stages of analysis, design, development, implementation, and evaluation. (2) The effectiveness results from the N-Gain percentage showed 56% in the “quite effective” category, as indicated by the teacher response test results of 96% and the student response test results of 86% in the “very feasible” category. Therefore, the use of the Arabic reading textbooks Al-Qirā'ah Al-Rasyīdah I is highly suitable for use in muṭāla'ah learning in the class VIII at MTs Muhammadiyah 2 Al-Munawwaroh Malang.